CLUSTER ANALYSIS AMONG NINE COTTON GENOTYPES - & et al., Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The field trial was conducted at Qwshtapa district , Grdmala village, which is 30 km far from center of  Erbil city to compare between nine genotypes of cotton (Gossipum hirsutum L) during the growing season 2016, the genotypes were (Coker 310, Lachata ‘Iraqi genotypes ’ Cafko, Dunn 1047, Montana, Stone Ville ‘ USA genotypes ‘, Bakhtegon, Khdorda , Vanamin   Iranian genotypes )  using randomized complete block design  (RCBD)with three replicates. any fertilizers were not added to the field during the research and Irrigation was done using Statistical analysis of the traits shown significant differences among genotypes , Coker 310 obtained  the highest value for  number of fruiting brunches, number of Bolls plant-1،Boll weight )g(, seed yield plant-1,  ginning% and oil% with values of (8.93  ,29.27,4.23, ,77.67, 39.87 and 28.33 ) respectively. Lashata genotype recorded highest value of protein and linoleic acid % which were (34.82 and 63.68) % respectively. Depending on growth stage, agronomic characteristics and their quality the genotypes were discerning to three main clusters, the first one included (Lachata and Stone Ville) genotypes, while the second clusters indicated only Cafko genotype and the third cluster included (Coker 310, Dunn 1047and, Montana, Bakhtegon , Khdorda and Vanamin) genotypes.